2020
DOI: 10.1021/acsomega.9b02816
|View full text |Cite
|
Sign up to set email alerts
|

Production of Sharp-Edged and Surface-Damaged Y2BaCuO5 by Ultrasound: Significant Improvement of Superconducting Performance of Infiltration Growth-Processed YBa2Cu3O7−δ Bulk Superconductors

Abstract: Growth and physical properties of bulk REBa2Cu3O7−δ (REBCO) superconductors fabricated by the infiltration growth (IG) method strongly depend on the initial size and morphology of the RE2BaCuO5 (211) particles. The present work details the novel method we developed for producing sharp-edged and surface-damaged 211 particles to be added to the REBCO bulks. We employed high-energy ultrasonic irradiation for pretreating the 211 particles and fabricated high-performance bulk single-grain YBa2Cu3O7−δ (YBCO) superco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…This can be seen in Figure 13 where, for a large commercial ring segment-shaped GdBaCuO bulk, a weak area of superconductivity can be seen during a field cooling magnetization at 77 K. Another method for preparing large size single crystal is the so-called infiltrationgrowth technique. This method requires a matrix of precursor materials, a liquid reactive material, and like for the TSMG, a seed on the top of the bulk [60][61][62]. Contrary to the TSMG method, it is easy to control the shape and the density of the precursor matrix and so the characteristics of the prepared superconducting bulk.…”
Section: Impact Of the Synthesis Process On Performancesmentioning
confidence: 99%
“…This can be seen in Figure 13 where, for a large commercial ring segment-shaped GdBaCuO bulk, a weak area of superconductivity can be seen during a field cooling magnetization at 77 K. Another method for preparing large size single crystal is the so-called infiltrationgrowth technique. This method requires a matrix of precursor materials, a liquid reactive material, and like for the TSMG, a seed on the top of the bulk [60][61][62]. Contrary to the TSMG method, it is easy to control the shape and the density of the precursor matrix and so the characteristics of the prepared superconducting bulk.…”
Section: Impact Of the Synthesis Process On Performancesmentioning
confidence: 99%
“…The J c and trapped fields of REBCO superconductors directly correlate with the microstructure achieved, therefore, controlling the growth and hence, the microstructure, is crucial to improve the superconducting properties [11][12][13][14][15]. This is due to the fact that J c in the REBCO materials is largely governed by flux pinning at the embedded RE211 particles.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is necessary to look for new and advanced methods of producing nanometer-sized RE211 phase particles within the RE123 matrix without using any chemical dopants. To overcome these problems, Pavan Kumar Naik et al [12,13] have demonstrated a new RE211 particle refinement method employing high energy ultrasonic radiation. This method was applied for the fabrication of YBCO bulk single grains by top-seeded IG process, and improvement of the superconducting properties were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Among, utilization of smaller sized 211 particles are beneficial for higher growth rates and embedding fine sized non-superconducting particles in Y123 bulk matrix. In this regard, in order to improve the flux pinning of REBCO superconductors, by a team of S. Pavan Kumar Naik et al, for the first time, a novel method of high-energy ultrasonic radiation was employed for pre-treating 211 powders [14][15]. Later this method is applied to other superconductors successfully and improved their performance [16].…”
Section: Introductionmentioning
confidence: 99%